Automated gonioscopy photography for iridocorneal angle grading. Issue 1 (January 2020) - Teixeira, Filipa; Sousa, David C; Leal, Inês; Barata, André; Neves, Carlos M; Pinto, Luís A
Purpose: The aim of this study is to assess the agreement between manual and automated gonioscopy for iridocorneal angle opening. Methods: The research is a cross-sectional observational study. Manual and automated gonioscopy were performed to consecutive patients in a glaucoma clinic. Iridocorneal angle opening grading was performed according to Shaffer's classification. Automated gonioscopy was performed with NGS-1 automated gonioscope (NIDEK Co., Gamagori, Japan). The automated gonio-photos were graded by two independent observers. Agreement between automated and manual gonioscopy and also among raters was ascertained by Fleiss' kappa statistic and comparison of area under curve. Results: In total, 88 eyes of 47 subjects were analysed. Mean age was 63 ± 10 years. Twenty eyes (22.7%) were excluded from grading due to poor quality images. Angle closure was detected in 23.4% with dynamic gonioscopy in comparison with 4.3% using automated image grading. The agreement for angle closure diagnosis between dynamic and automated gonioscopy was low (κ = 0.09 ± 0.10; p = 0.18). The area under curve for detecting eyes with angle closure showed poor accuracy between automated and manual methods (area under curve: 0.53 ± 0.05, 95% confidence interval: 0.44–0.62). There was modest inter-rater agreement for angle opening assessment of automated images with Fleiss' kappa of 0.17 (95% confidence interval: 0.035–0.238). Conclusion: Manual and automated gonioscopy showed only slight agreement for the assessment of iridocorneal angle opening status. Further improvements of the NGS-1 automated gonioscopy and technique are desired for widespread use in a real-life setting.